PENGEMBANGAN KURIKULUM SEKOLAH BERBASIS KEWIRAUSAHAAN DI SMA NEGERI 1 TEMON - Raden Praja Aby Choiri Hasbi; Fitri Nur Mahmudah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The aim of this study is to determine and analyze: (1) Entrepreneruship-based curriculum planning; (2) Implementation of entrepreneruship-based curriculum; and (3) Evaluation of entrepreneruship-based curriculum in SMAN 1 Temon. This research is used qualitative study. Data collection techniques by obsercation, interview, and documentation. Research result, (1) Planning for entrepreneruship-based curriculum begins by determining the curriculum structure that will become planning, after the formation of the structure, the concept of structure which consists of the background, objectives, scope, competency standards, and basic competencies needed is considered. (2) The implementation of the entrepreneurship-based curriculum must regulate the stages in each class of students by the curriculum documents that have been prepared, each learning process is always integrated with aspects of entrepreneurship and some that produce products as learning outcomes. (3) Evaluation is carried out based on school quality objectives and taking into account the dimensions of the program and implementation. Keywords: entrepreneruship-based curriculum, curriculum, education